THE EFFECT OF HEALTH EDUCATION ABOUT CONTRACEPTION ON HUSBAND'S INTEREST IN VASECTOMY - Nur Maziyah Hurin’in Hurin'in; Tri Yunita Fitria Damayanti Damayanti (International Journal of Midwifery Research, 2021)
Men who do not have sufficient knowledge about family planning will not be motivated to participate in using contraception. This research is a Pre-Experimental Design research with a pretest-posttest approach. The intervention used was in the form of providing health education about contraception to men in the male group (husbands) who met the inclusion criteria in Karangsari Village, Tuban District, Tuban Regency. The study population was 50 men (husbands) who met the inclusion criteria in Karangsari Village, Tuban District, Tuban Regency in June 2021. Sampling in this study is a non-probability sample with purposive sampling technique. The desired criteria in this study are men (husbands) who meet the inclusion criteria in Karangsari Village, Tuban District, Tuban Regency as many as 50 people in June 2021. Data analysis used in this study is to use the McNemar Test with the help of SPSS with a significant limit of p-value <0.05. The results of the study after the post-test, almost all respondents still chose not to be interested in doing a vasectomy, namely 43 (86%), there were only 4 respondents who were interested after health education was not interested and were given health education. The analysis using the McNemar Test statistical test obtained a p-value = 0.125, because the p-value > 0.05 which indicates only a few are interested, there is no significant increase in interest in using a vasectomy before and after giving education about contraception.